2015
DOI: 10.3389/fpls.2015.01114
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Arabidopsis Hexokinase in Citrus Guard Cells Controls Stomatal Aperture and Reduces Transpiration

Abstract: Hexokinase (HXK) is a sugar-phosphorylating enzyme involved in sugar-sensing. It has recently been shown that HXK in guard cells mediates stomatal closure and coordinates photosynthesis with transpiration in the annual species tomato and Arabidopsis. To examine the role of HXK in the control of the stomatal movement of perennial plants, we generated citrus plants that express Arabidopsis HXK1 (AtHXK1) under KST1, a guard cell-specific promoter. The expression of KST1 in the guard cells of citrus plants has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 55 publications
6
87
0
Order By: Relevance
“…The first evidence for this alternative mechanism is that the addition of 100 mM sucrose induces stomatal closure via HXK activity and guard cell nitric oxide accumulation, a component of the ABA signalling pathway. Transgenic A. thaliana, Solanum lycopersicum and Citrus sinensis plants overexpressing HXK1 under control of the inward rectifying K + channel (KST1) promoter, which drives guard cell-specific expression, show higher stomatal closure via a pathway induced by sugar and mediated by ABA (Kelly et al, 2013;Lugassi et al, 2015). These data suggest that sucrose and HXK activity could represent a possible mechanism that induces stomatal closure during periods of high photosynthetic rates (Kelly et al, 2013).…”
Section: Role Of Mesophyll-derived Sucrose In Stomatal Closurementioning
confidence: 99%
See 2 more Smart Citations
“…The first evidence for this alternative mechanism is that the addition of 100 mM sucrose induces stomatal closure via HXK activity and guard cell nitric oxide accumulation, a component of the ABA signalling pathway. Transgenic A. thaliana, Solanum lycopersicum and Citrus sinensis plants overexpressing HXK1 under control of the inward rectifying K + channel (KST1) promoter, which drives guard cell-specific expression, show higher stomatal closure via a pathway induced by sugar and mediated by ABA (Kelly et al, 2013;Lugassi et al, 2015). These data suggest that sucrose and HXK activity could represent a possible mechanism that induces stomatal closure during periods of high photosynthetic rates (Kelly et al, 2013).…”
Section: Role Of Mesophyll-derived Sucrose In Stomatal Closurementioning
confidence: 99%
“…The idea that sucrose acts as a mesophyll‐to‐guard cell connector is strongly supported by experiments in which labelled 14 CO 2 provided to mesophyll cells was detected at the apoplastic space of guard cells as sucrose (Lu et al ., ). Furthermore, it has been shown that sucrose accumulation in the guard cell apoplast of phloem loader species (Lu et al ., ), or its dissimilation within guard cells (Kelly et al ., ; Lugassi et al ., ), induces stomatal closure in periods of high photosynthetic rate. These results suggest that guard cells import sucrose from the apoplastic space and that the majority, if not all, comes from surrounding mesophyll cells (Fig.…”
Section: The Role Of Sucrose As a Mesophyll‐to‐guard Cell Connectormentioning
confidence: 99%
See 1 more Smart Citation
“…photosynthesis (for review, see Lugassi et al, 2015;Daloso et al, 2016;Santelia and Lawson, 2016;Santelia and Lunn, 2017). By the end of the day, the slow response of g s can result in the maintenance of high g s , which leads to substantial water losses that are not accompanied by any carbon uptake (Blom-Zandstra et al, 1995).…”
Section: Diurnal Impact On Stomatal Behavior and Implications For Futmentioning
confidence: 99%
“…The roles of HXKs could be summarized in participation to the juvenile-to-adult transition, to the uptake of minerals, mainly phosphates, to the short-term (reversible) sugar-sensing regulation and to the long-term growth-inhibiting effect in case of constitutive expression of AtHXK1 under the 35S promoter in Arabidopsis and tomato plants . However, recent studies with citrus, tomato and Arabidopsis have shown that HXK is involved in guard cells control and provokes stomatal closure independent of its osmotic effect Lugassi et al, 2015). It is not yet known if in strawberry the MAKRs (membrane associated kinase regulators) could be directly involved in the same metabolic pathway.…”
Section: Introductionmentioning
confidence: 99%